Human Existence as Individual Creature Based on Robert Frost’s Poems, "Stopping by Woods on a Snowy Evening" and "the Road Not Taken", Through Stylistic View - Jumino Jumino (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Abstract This article deals with human existence as individual creature in the world based on Robert Frost’s poem ”Stopping By Woods on A Snowy Evening” and ”The Road Not Taken”. In doing research, the writer used method of collecting and analyzing data. Observation through document study was used to collect data. While descriptive qualitative method was used to analayze the data. The result shows that both pooems, through poetic device and figurative language used, tell the readers about the responsibilities of human life to do before he os she dies. These may be reponsibilities of any duties and choices in human life. Through the first poem, Robert Frost reminds human being for having forgotten his or her duties in life. Then through the second poem,  the poet emphasizes the importaance of making choices and its consequences of the choices. Key words: human existence, creature, life, choice, duty